What are the differences in patient-reported functional outcomes and recovery time between arthroscopic and open surgical repair for full-thickness rotator cuff tears in adults ? : A Systematic Review - Virta Andhika; Mohammad Erstda Trapsilantya (International Medical Journal Corp. Ltd, 2025)
Introduction: Full-thickness rotator cuff tears are a major cause of shoulder pain and disability, commonly treated with either open or arthroscopic surgical repair. The optimal surgical approach remains debated, with extensive research comparing the two techniques. This systematic review aims to consolidate current evidence on the differences in patient-reported functional outcomes, recovery time, and complication rates between arthroscopic and open repair for full-thickness rotator cuff tears in adults. Methods: A systematic review was conducted following PRISMA guidelines. We searched PubMed, Springer, Semantic Scholar, Google Scholar, and Wiley Online Library for comparative studies published since 2015. The search used keywords based on the PICO framework, including